Answers

2014-05-01T15:35:35+05:30
Ydx-xdy+logxdx                                                                                                                    ydx-xdy=-logx                                                                                                            dy/dx=logx/xy      
0
2014-05-01T15:59:34+05:30
ydx+log(x)dx=xdy  \\   \frac{log(x)}{x} = \frac{dy}{dx}-\frac{y}{x}
this equation is in linear with x
I.F=e^{ \int\limits { \frac{-1}{x} } \, dx }=e{-logx}=e{log( \frac{1}{x} )}= \frac{1}{x}
so solution is
 \frac{y}{x} = \int\limits { \frac{log(x)}{x^2} } \, dx+C \\  \frac{y}{x} = \frac{log(x)}{-x} + \int\limits { \frac{log(x)}{x}} \, dx+C \\   \frac{y}{x} = \frac{log(x)}{-x} + \int\limits { \frac{log(x)}{x}} \, dx+C \\  \frac{y}{x} = \frac{log(x)}{-x} + (log(x))^2+C
0